Kontroversi Theosofi Islam Jawa dalam Manuskrip Kapujanggan - Muhammad Irfan Riyadi (IAIN Ponorogo, 2013)
Abstract: The discourse of Islamic Sufism thought in Java noted that the dynamics of the Islamic theosofi find his partner in the face of Javanese mystical thought. Islamic Sufism that puts the elements of sharia religious mysticism called Sufism shar’i or ortodoks sufism; while the advanced elements of philosophy called philosophical Sufism, this pattern is manifest that acculturative with mystical Javanese syncretic also known as heterodoks Sufism. In Javanese manuscripts poet, those patterns of sufism are always in dialogue (dialectic) from time to time; since the 15th century until the 19th century or from era of sainthood untuil era poet (Pujangga) Kraton Surakarta. The dialectic wide variety of books including recorded in Suluk Siti jenar, Suluk Dharmo Gandul, Suluk Sumirang, Sastra Gending, Serat Cabolek, Serat Centhini and Suluk Saloka Jiwa. This paper explores the controversial thought for between Islamic Sufism and Javanese theosofi thinking in these manuscripts. For that purpose, this study uses the theory of dialectics to explain the two ideas above dialogue by placing the poet as disseminator between the two cultures so was born a series of local wisdom in the form of a unique synthesis, elucidation of the role of the poet will be presented with the theory of cultural articulation. The conclusion of this paper is that a dialectic synthesis between Islam and Javanese mysticism theosofi was birth Kejawen institution thought, this thought was appear in religious communities in Java, a new institution with cultural psychotherapy and that applied by the community namely abangans, this institution growth supported by culture of Javanese palace tradition and spirit. Pujangga played a central role as interpreters of Islamic Sufism in the context of locality to realize a peaceful penetration.